2015
DOI: 10.1021/acs.jnatprod.5b00487
|View full text |Cite
|
Sign up to set email alerts
|

Aspertetranones A–D, Putative Meroterpenoids from the Marine Algal-Associated Fungus Aspergillus sp. ZL0-1b14

Abstract: Aspertetranones A-D (1-4), four new highly oxygenated putative rearranged triketide-sesquiterpenoid meroterpenes, were isolated from the marine algal-associated fungus Aspergillus sp. ZL0-1b14. On the basis of a comprehensive spectroscopic analysis, the planar structures of aspertetranones were determined to possess an unusual skeleton in the terpenoid part. The relative and absolute configurations of the aspertetranones were assigned on the basis of NOESY analysis, X-ray crystallography, and circular dichrois… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
28
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 26 publications
(29 citation statements)
references
References 15 publications
(21 reference statements)
1
28
0
Order By: Relevance
“…Where the absolute conguration has been determined for all stereocentres in a compound, the identifying diagram number is distinguished by addition of the † symbol. The new format for this review introduced for the previous review 1 has been retained, with only a selection of highlighted structures (197) now shown in the review. Compound numbers for structures not highlighted in the review are italicised, and all structures are available for viewing, along with their names, taxonomic origins, locations for collections, and biological activities, in a ESI † † document associated with this review.…”
Section: Introductionmentioning
confidence: 99%
“…Where the absolute conguration has been determined for all stereocentres in a compound, the identifying diagram number is distinguished by addition of the † symbol. The new format for this review introduced for the previous review 1 has been retained, with only a selection of highlighted structures (197) now shown in the review. Compound numbers for structures not highlighted in the review are italicised, and all structures are available for viewing, along with their names, taxonomic origins, locations for collections, and biological activities, in a ESI † † document associated with this review.…”
Section: Introductionmentioning
confidence: 99%
“…Comparison of the optical rotation value, NMR chemical shifts, and ROESY correlations of 1 with those of ochraceopone E suggested that these compounds have the same absolute stereochemistry. This result was also supported by the fact that ochraceopones [ 19 , 23 ] share a biosynthetic pathway.…”
Section: Resultsmentioning
confidence: 68%
“…In preliminary screening, this strain showed good bioactivities such as antimicrobial and antifungal properties. The crude extract of the strain was purified further by a reversed-phase HPLC to yield one new compound, ochraceopone F ( 1 ), and four known compounds ( Figures S8–S19 ), aspertetranone D ( 2 ) [ 19 ], cycloechinulin ( 3 ) [ 20 ], wasabidienone E ( 4 ) [ 21 ], and mactanamide ( 5 ) [ 22 ] ( Figure 1 ). The structures of the known compounds were identified by 1D and 2D NMR analysis and comparison with literature data.…”
Section: Introductionmentioning
confidence: 99%
“…In contrast to the marine compounds with described anti-inflammatory mechanisms of action described in the preceding paragraph, and as shown in Table 2, for marine compounds , only anti-inflammatory activity (IC 50 ) was reported, but the molecular mechanism of action of these marine-derived compounds remained undetermined at the time of publication: a new highly oxygenated meroterpene aspertetranone D (164) isolated from the marine algal-associated fungus Aspergillus sp. ZL0-1b14 [184]; a novel 6,12-dichlorobriarene diterpenoid briarenolide J (165), two briarane diterpenoids briarenolides K and L (166,167), and the briarenolides U-W (168)(169), all compounds isolated from the Taiwanese octocoral Briareum sp. [185][186][187]; two new briarane diterpenoids briaviolides E and I (170,171), isolated from the Taiwanese soft coral Briareum violacea [188]; a new pigmented phenazine compound dermacozine H (172), isolated from the actinomycete Dermacoccus abyssi sp.…”
Section: Anti-inflammatory Activitymentioning
confidence: 99%
“…[185][186][187]; two new briarane diterpenoids briaviolides E and I (170,171), isolated from the Taiwanese soft coral Briareum violacea [188]; a new pigmented phenazine compound dermacozine H (172), isolated from the actinomycete Dermacoccus abyssi sp. nov. strain MT1.1, isolated from a Mariana Trench sediment at a depth of 10,898 m [189]; a novel sesquiterpene dysifragilone A (173), isolated from the South China Sea sponge Dysidea fragilis [190]; a new xenicane 4α-hydroxypachylactone (174), isolated from a Chinese brown alga Dictyota plectens [191]; a polyketide comaparvin (175), isolated from the Taiwanese marine crinoid Comanthus bennetti [192]; two novel eunicellin-type diterpenoids hirsutalins N and S (176, 177) and a new tocopherol-derived metabolite hirsutocospiro A (178), isolated from the Taiwanese soft coral Cladiella hirsuta [193][194][195]; a new cembranoid isosinulaflexiolide K (179), isolated from cultured Taiwanese soft corals Sinularia sandensis and Sinularia flexibilis [196]; a novel 9,11-secogorgosteroid klyflaccisteroid F (180), isolated from the Taiwaneses soft coral Klyxum flaccidum [197]; new eunicellin-type diterpenoids krempfielins N (181), Q (182), and R (183), isolated from a Taiwanese soft coral Cladiella krempfi [198,199]; a methylfarnesylquinone (184), isolated from the Taiwanese marine brown alga Homeostrichus formosana [200]; a novel steroid monanchosterol B (185), isolated from the Korean sponge Monanchora sp. [201]; a oxygenated steroid derivative (186), isolated from the Vietnamese starfish Protoreaster nodosus [202]; a new spirobisnaphthalene rhytidenone C (187), isolated from an extract of a cultured fungal endophyte Rhytidhysteron sp.…”
Section: Anti-inflammatory Activitymentioning
confidence: 99%